How small firms build resilience to ward off crises: a paradox perspective - Chaudhary, Sanjay; Dhir, Amandeep; Meenakshi, N.; Christofi, Michael (My University, 2024)
Despite crises being a dominant theme in organizational research, little inquiry has been conducted into how small firms built resilience and coped with uncertainties created by the COVID-19 pandemic. In this study, we explore the challenges faced by small firms during this crisis and how they handled it and built resilience. We collected qualitative data using the open-ended essay method to answer our research questions. Findings reveal that small firms encountered challenges that were predominantly related to employees, technology, and liquidity. Three key paradoxes also emerged during the crisis: short-term and long-term performance, efficiency and adaptability, and safety and profit. The findings further revealed that small firms employed digitalization, prior and new knowledge, and leadership to cope with these challenges. By elucidating these challenges and coping strategies, the research contributes to the existing literature on resilience in small firms. Our findings emphasize that the survival prospects of small firms during the COVID-19 crisis depended on understanding potential paradoxes that needed to be resolved and utilizing the coping mechanisms developed to build resilience.
Keywords: Disruptions; Crises; Organizational resilience; Challenges; Paradox; Coping; Digitalization; Small firms